1996
DOI: 10.1111/j.1439-0442.1996.tb00491.x
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of Ketone Bodies in Energy Metabolism of Dairy Cows: A Review

Abstract: Increased lipolysis, low insulin/glucagon ratios and malonyl-CoA concentrations are prerequisites for ketogenesis. From an aetiological viewpoint, there are two quite different types of metabolic drsorders in which ketosis can occur, the hypoglycaemic-hypoinsulinaemic and the hyperglycaemic-hyperinsulinaemic type. The former, Type I, generally occurs 3-6 weeks after calving in cows whose milk secretion is so extensive that the demand for glucose exceeds the capacity for glucose production. To protect the body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
112
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 35 publications
9
112
1
4
Order By: Relevance
“…However, in our study it was BHBA concentrations that were found to have the strongest genetic correlation with reproductive traits. In the liver, NEFA can be esterified to triglycerides, enter the citric acid cycle, or form ketone bodies (Holtenius and Holtenius, 1996). High rates of ketogenesis and high blood BHBA concentrations can be considered as cow's failure to adapt to negative energy balance (Herdt, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study it was BHBA concentrations that were found to have the strongest genetic correlation with reproductive traits. In the liver, NEFA can be esterified to triglycerides, enter the citric acid cycle, or form ketone bodies (Holtenius and Holtenius, 1996). High rates of ketogenesis and high blood BHBA concentrations can be considered as cow's failure to adapt to negative energy balance (Herdt, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The δ5.5-9.0 region (dashed box) was magnified 10 times relative to the δ0.5-5.5 region for clarity. The samples K 1-15 , K 1-16 , K 2-8 , K [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , and C 8 were removed to achieve a better quality of spectrum and a better suppression effect of the water peak. The data were subsequently analyzed using multivariate statistics (PCA and OPLS-DA).…”
Section: H-nmr Spectroscopy Of Plasma Samplesmentioning
confidence: 99%
“…There are two types of ketosis: clinical ketosis and subclinical ketosis, based on the clinical symptoms, e.g., anorexia, depression, decreased milk production, constipation, drowsiness or nervousness [3], and plasma 3-hydroxybutyrate acid levels (BHBA, >1.20 mmol/L) [4]. However, Holtenius et al [5] reported that ketosis in dairy cattle is divided into types I and II based on the disease characteristics and clinical features. Type I ketosis, which is mainly attributed to the absence of gluconeogenic precursors, is also termed secondary ketosis, alimentary ketosis, starvation ketosis, and special nutritional deficiency ketosis.…”
Section: Introductionmentioning
confidence: 99%
“…Stentz [15] suggested that insulin binding, processing and responsiveness in mitogen-activated T-cells were reflective of the donor's glycemic status and ambient insulin levels in insulin resistant states. A previous investigation has shown that there is reduced sensitivity to insulin in overfed normal periparturient cows [10]. Depression of insulin sensitivity in peripheral tissues, including the liver, is recognized as a factor that induces fatty liver in dairy cows.…”
mentioning
confidence: 98%
“…Overfeeding during the dry period leads to increased levels of nonesterified fatty acids (NEFA) lipolysis in adipose tissues generating a risk of development of fatty liver [10,13]. Decreased insulin sensitivity has been detected in hyperketotic cows with periparturient metabolic disease [8,16].…”
mentioning
confidence: 99%